Collins English dictionary (Glasgow, 2005)
Thousands of new words have been added to this thumb-indexed edition of the Collins English Dictionary. Latest new editions include the definitions of aquaerobics, cardboard city, chaos theory, pro-choice, shell suit, snowboarding, virtual reality and white-knuckle.
Keywords: English language -- Dictionaries